Carbon fiber-based electrode of flow battery and preparation method of carbon fiber-based electrode
By designing a uniform density bus hole on the electrode side of the carbon fiber-based electrode of the flow battery, the problem of electrolyte flow is solved, the electrochemical reaction speed and voltage efficiency are improved, and the performance of the flow battery is improved. The method is stable. , suitable for large-scale production.
Patent Information
- Application Number
- CN202411478927.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The lack of effective bus holes inside the carbon fiber-based electrode of existing flow batteries, resulting in the hindered flow of the electrolyte, affecting the reaction speed and voltage efficiency.
A bus hole with uniform density is opened on the surface of the electrode substrate, and an electrolyte transmission channel is formed during the carbonization process by using the pore-making filler to ensure that the electrolyte can flow effectively to the diaphragm side.
It improves the mass transfer ability of the electrolyte, accelerates the transmission of active substances, reduces the thickness of the ion transport layer on the surface of the electrode on the side of the diaphragm, improves the electrochemical reaction speed and voltage efficiency, and improves the overall performance of the flow battery. The preparation method is simple, Suitable for large-scale production and reduces production costs.
Smart Images

Figure CN119181819A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid flow batteries, and in particular to a liquid flow battery carbon fiber-based electrode and a preparation method thereof. Background Art
[0002] As a green secondary battery, flow battery is widely used in large-scale energy storage systems due to its high energy density, long cycle life and good safety. As a key component of flow battery, the performance of electrode directly affects the overall performance of flow battery. Carbon fiber-based electrodes have become the main choice of flow battery electrodes due to their excellent conductivity and stability. The existing preparation methods of carbon fiber-based electrodes mainly include pre-oxidation stage and carbonization graphitization stage. In the pre-oxidation stage, carbon fiber undergoes cyclization, dehydrogenation, oxidation and other processes to form carbon fiber with polymer properties. In the carbonization graphitization stage, carbon fiber undergoes shrinkage and structural transformation to form carbon fiber with strong rigidity. However, in the above, the existing electrode lacks effective confluence pores, which leads to the obstruction of electrolyte flow inside the electrode, affecting the convective mass transfer of electrolyte to the diaphragm side, and further affecting the reaction rate and voltage efficiency of the flow battery. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a carbon fiber-based electrode for a liquid flow battery and a preparation method thereof, so as to solve the technical problems mentioned in the prior art.
[0004] A carbon fiber-based electrode for a flow battery, comprising an electrode substrate, a surface of the electrode substrate being provided with a plurality of confluence holes to form an electrolyte transmission channel on the electrode side of the electrode substrate for the electrolyte to flow from the electrode side to the diaphragm side;
[0005] The confluence holes are formed by carbonizing and forming holes on the surface of the electrode substrate using a pore-forming filler.
[0006] Optionally, the density of the confluence holes is 1-15 / cm 2 ;
[0007] Preferably, the diameter of the confluence hole is 0.2-3 mm.
[0008] Optionally, the thickness of the electrode substrate is 0.5-5 mm;
[0009] Preferably, the depth of the conduit hole is at least half of the thickness of the electrode substrate.
[0010] A method for preparing a carbon fiber-based electrode for a flow battery, the method comprising the following steps:
[0011] Selecting an electrode substrate raw material, and inserting a pore-forming filler on the surface of the electrode substrate raw material;
[0012] Carbonizing the electrode substrate raw material with the pore-forming filler inserted therein, so that a pore structure is formed at a portion of the surface of the electrode substrate raw material with the pore-forming filler inserted therein;
[0013] The electrode substrate raw material containing the pore structure is graphitized to obtain the carbon fiber-based electrode for the liquid flow battery.
[0014] Optionally, the electrode substrate raw material is a carbon-based precursor material;
[0015] The carbon-based precursor material is polyacrylonitrile-based carbon felt, polyacrylonitrile-based graphite felt, polyacrylonitrile-based carbon cloth or polyacrylonitrile-based carbon paper;
[0016] Preferably, the thickness of the carbon-based precursor material is 0.8-10 mm.
[0017] Optionally, the method further comprises: before inserting the pore-forming filler into the surface of the electrode substrate raw material, performing a pre-oxidation treatment on the electrode substrate raw material;
[0018] The pre-oxidation treatment conditions are: oxidation treatment at 270-290° C. for 85-95 minutes in an air atmosphere.
[0019] Optionally, the pore-forming filler is made of a material that does not deform during high-temperature sintering and does not undergo a carbonization reaction;
[0020] Preferably, the pore-forming filler is made of carbon-based material;
[0021] Further preferably, the pore-forming filler is a carbon fiber bundle or a high-carbon needle.
[0022] Optionally, the diameter of the pore-forming filler is 1-3 mm;
[0023] Preferably, the penetration depth of the pore-forming filler is at least half of the thickness of the electrode substrate raw material.
[0024] Optionally, the carbonization treatment conditions are:
[0025] The carbonization temperature is 950-1050°C and the carbonization time is 1.8-2.2h;
[0026] Preferably, the carbonization treatment is carried out under a protective atmosphere.
[0027] Optionally, the conditions for the graphitization treatment are:
[0028] The graphitization treatment temperature is 1900-2300°C, and the graphitization treatment time is 1-3h;
[0029] Preferably, the graphitization treatment is performed under a protective atmosphere.
[0030] The beneficial effects that the present invention can produce include:
[0031] The present invention provides a liquid flow battery carbon fiber-based electrode and a preparation method thereof, by designing a uniform density of confluence holes on the electrode side of the liquid flow battery carbon fiber-based electrode, so as to improve the electrolyte mass transfer capacity of the liquid flow battery carbon fiber-based electrode in the direction perpendicular to the diaphragm, accelerate the rapid transmission of active substances in the near-diaphragm interval, reduce the thickness of the ion transport layer on the surface of the electrode on the diaphragm side, increase the electrochemical reaction rate, reduce the polarization caused by mass transfer, and improve the voltage efficiency and electrolyte utilization rate during the charging and discharging process, so as to solve the problem of electrolyte flow obstruction inside the electrode in the prior art and improve the overall performance of the liquid flow battery. Among them, the confluence holes in the preparation method adopt a hot forming method, which can avoid the fiber breakage, felt structure damage and hole rebound problems of the carbon fiber electrode during the post-processing process, and have a stability that is not weaker than that of the electrode without a hole. In addition, the preparation method is simple, easy to operate, suitable for large-scale production, can reduce production costs, and improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic flow diagram of a method for preparing a carbon fiber-based electrode for a flow battery according to the present invention;
[0033] Figure 2 This is a schematic diagram of the structure of a carbon fiber-based electrode for a flow battery of the present invention;
[0034] In the figure: 1. electrode substrate, 2. conduit hole. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] See also Figure 1As shown, the present invention provides a method for preparing a carbon fiber-based electrode for a liquid flow battery, and the preparation method includes the following steps: Step 1, pre-oxidation stage: select a carbon-based precursor material of a preset thickness as an electrode substrate raw material, and subject the electrode substrate raw material to a pre-oxidation treatment, wherein the treatment conditions are: in an air atmosphere, oxidize at 270-290°C for 85-95 minutes to form a pre-oxidized fiber felt with polymer properties; Step 2, manufacture of a collection hole 2: uniformly insert a plurality of high-carbon needles or carbon fiber bundles as pore-forming fillers in the vertical direction on the surface of the pre-oxidized fiber felt to ensure that the collection hole 2 formed on the surface of the carbon fiber-based electrode of the liquid flow battery has the shortest electrolyte transmission path and the smallest pressure loss; Step 3, carbonization stage: insert the pre-oxidized fiber felt pierced with pore-forming fillers Put it into a carbonization furnace, and carbonize the preoxidized fiber felt at 950-1050℃ for 1.8-2.2h under a protective atmosphere to form an inherent and non-rebound pore structure on the surface of the preoxidized fiber felt; wherein, the pore-forming filler generates internal stress in the preoxidized fiber felt during the heat treatment process, so that the fibers of the preoxidized fiber felt are naturally twisted during the contraction and structural transformation process, forming an inherent and non-rebound pore structure, and serving as a hole for the electrolyte of the flow battery to be transmitted to the diaphragm; Step 4, graphitization stage: take out the pore-forming filler in the preoxidized fiber felt, and put the preoxidized fiber felt into a graphitization furnace, and carry out high-temperature graphitization treatment at 1900-2300℃ under a protective atmosphere for 1-3h to obtain a flow battery carbon fiber-based electrode with a confluence hole 2. In the above, the carbon-based precursor material is polyacrylonitrile-based carbon felt, polyacrylonitrile-based graphite felt, polyacrylonitrile-based carbon cloth or polyacrylonitrile-based carbon paper. The thickness of the carbon-based precursor material is 0.8-10 mm, the diameter of the pore-forming filler is 1-3 mm, and the density of the pore-forming filler is 1-2 pieces / cm 2 The penetration depth of the pore-forming filler is at least half of the thickness of the electrode substrate raw material. The protective atmosphere of the carbonization furnace and the graphitization furnace is nitrogen, helium or argon.
[0037] It should be noted that, in this embodiment, the carbon-based precursor material will shrink during the carbonization process, shrinking by 40% to 50% in the thickness direction. After the pore-forming filler is taken out, during the graphitization stage, the pre-oxidized fiber felt will shrink slightly under inherent stress, so that the pore size of the confluence hole 2 is slightly smaller than the diameter of the pore-forming filler.
[0038] See also Figure 2As shown, the present invention also provides a carbon fiber-based electrode for a liquid flow battery, which is made by the above method. The carbon fiber-based electrode for a liquid flow battery includes an electrode substrate 1, and a plurality of confluence holes 2 are evenly opened on the surface of the electrode substrate 1 to form an electrolyte transmission channel on the electrode side of the electrode substrate 1 for the electrolyte to flow from the electrode side to the diaphragm side; wherein the confluence holes 2 are formed by carbonizing and forming holes on the surface of the electrode substrate 1 using a pore-forming filler. Specifically, the thickness of the electrode substrate 1 is 0.5-5 mm, and the density of the confluence holes 2 is 1-15 / cm 2 The diameter of the conduit hole 2 is 0.2-3 mm, and the depth of the conduit hole 2 is at least half of the thickness of the electrode substrate 1.
[0039] Example 1: Pre-oxidation stage: Select polyacrylonitrile-based carbon felt with a thickness of 5 mm as the electrode substrate raw material, and pre-oxidize the electrode substrate raw material at 285°C for 90 minutes to form a pre-oxidized fiber felt with polymer properties; Make confluence holes 2: Insert multiple high-carbon needles or carbon fiber bundles with a diameter of 2 mm in a rectangular array in the vertical direction on the surface of the pre-oxidized fiber felt as pore-forming fillers, wherein the density of the pore-forming filler is 1 needle / cm 2 , the penetration depth is 4mm; carbonization stage: put the pre-oxidized fiber felt with pore-forming filler into the carbonization furnace, heat it to 1020℃ and carry out carbonization treatment for 2h to form inherent and non-rebound confluence pores 2 on the surface of the pre-oxidized fiber felt; graphitization stage: take out the pore-forming filler in the pre-oxidized fiber felt, and put the pre-oxidized fiber felt into the graphitization furnace and heat it to 2150℃ for high-temperature graphitization treatment for 1h to obtain the carbon fiber-based electrode for the flow battery. Specifically, the thickness of the carbon fiber-based electrode for the flow battery is 2.5mm, and the density of the confluence pores 2 is 2.5
[0040] / cm 2 The diameter of the confluence hole 2 is 1.5 mm, and the depth of the confluence hole 2 is 2.0 mm.
[0041] Example 2: Pre-oxidation stage: Select polyacrylonitrile-based carbon felt with a thickness of 5 mm as the electrode substrate raw material, and pre-oxidize the electrode substrate raw material at 280°C for 90 minutes to form a pre-oxidized fiber felt with polymer properties; Make confluence holes 2: Insert multiple high-carbon needles or carbon fiber bundles with a diameter of 2 mm in a rectangular array vertically on the surface of the pre-oxidized fiber felt as pore-forming fillers, wherein the density of the pore-forming filler is 2.5 needles / cm 2, the penetration depth is 4mm; carbonization stage: put the preoxidized fiber felt with pore-forming filler into the carbonization furnace, heat it to 1000℃ and perform carbonization treatment for 2h to form inherent and non-rebound confluence pores 2 on the surface of the preoxidized fiber felt; graphitization stage: take out the pore-forming filler in the preoxidized fiber felt, and put the preoxidized fiber felt into the graphitization furnace and heat it to 2200℃ for high-temperature graphitization treatment for 1h to obtain the carbon fiber-based electrode for the flow battery. Specifically, the thickness of the carbon fiber-based electrode for the flow battery is 2.5mm, and the density of the confluence pores 2 is 2.5 / cm 2 The diameter of the confluence hole 2 is 1.5 mm, and the depth of the confluence hole 2 is 2.0 mm.
[0042] Example 3: The difference from Example 1 is that the diameter of the pore-forming filler is 2 mm, and the penetration depth of the pore-forming filler is 3.6 mm. Specifically, the thickness of the carbon fiber-based electrode of the flow battery is 2.5 mm, and the density of the confluence holes 2 is 2 / cm 2 The diameter of the confluence hole 2 is 1.5 mm, and the depth of the confluence hole 2 is 1.8 mm.
[0043] Example 4: The difference from Example 1 is that the density of the pore-forming filler is 2 pieces / cm 2 The diameter of the pore-forming filler is 3 mm, and the penetration depth of the pore-forming filler is 3.2 mm. Specifically, the thickness of the carbon fiber-based electrode of the flow battery is 2.5 mm, and the density of the confluence pores 2 is 2 / cm 2 The diameter of the confluence hole 2 is 2.3 mm, and the depth of the confluence hole 2 is 1.6 mm.
[0044] Example 5: The difference from Example 1 is that the density of the pore-forming filler is 1.5 pieces / cm 2 The diameter of the pore-forming filler is 3 mm, and the penetration depth of the pore-forming filler is 3.2 mm. Specifically, the thickness of the carbon fiber-based electrode of the flow battery is 2.5 mm, and the density of the confluence pores 2 is 1.5 / cm 2 The diameter of the confluence hole 2 is 2.3 mm, and the depth of the confluence hole 2 is 1.6 mm.
[0045] Comparative Example 1: A polyacrylonitrile fiber felt with a thickness of 5 mm was selected and subjected to pre-oxidation, carbonization and graphitization treatments by the same process to form a carbon fiber-based electrode for a liquid flow battery with polymer properties.
[0046] In the above, the carbon fiber-based electrodes of the flow batteries prepared in Examples 1-5 and Comparative Example 1 were used as the positive electrode or negative electrode of the flow battery to test the overall performance of the battery, and the test results are shown in Table 1:
[0047] Table 1
[0048]
[0049]
[0050] As can be seen from Table 1, the present invention designs a uniform density of confluence holes 2 on the electrode side of the carbon fiber-based electrode of the flow battery to improve the electrolyte mass transfer capacity of the carbon fiber-based electrode of the flow battery in the direction perpendicular to the diaphragm, accelerate the rapid transmission of active substances in the near-diaphragm interval, reduce the thickness of the ion transport layer on the surface of the electrode on the diaphragm side, increase the electrochemical reaction rate, reduce the polarization caused by mass transfer, and improve the voltage efficiency and electrolyte utilization rate during the charge and discharge process, so as to solve the problem of electrolyte flow obstruction inside the electrode in the prior art and improve the overall performance of the flow battery. Among them, the confluence holes 2 in the preparation method adopt a hot forming method, which can avoid fiber breakage, felt structure damage and hole rebound problems in the carbon fiber electrode during the post-processing process, and has a stability that is not weaker than that of the electrode without a hole. In addition, the preparation method is simple, easy to operate, suitable for large-scale production, and can reduce production costs and improve production efficiency.
[0051] Specifically, the corresponding needle plate can be designed according to the design density of the confluence holes 2 on the surface of the electrode substrate 1, as well as the aperture size and hole depth, so as to improve the optimization of the piercing depth by controlling the needle density of the needle plate and the size of the needle head, and then regulate to meet the different needs of the liquid flow battery electrode, such as the arrangement of the confluence holes 2 can be set in a uniform array in the shape of a rectangle, diamond, triangle, etc., and the distribution density of the confluence holes 2 can be adjusted.
Claims
1. A carbon fiber-based electrode for a flow battery, characterized in that: The carbon fiber-based electrode for a liquid flow battery comprises an electrode substrate (1), a surface of the electrode substrate (1) being provided with a plurality of confluence holes (2) so as to form an electrolyte transmission channel on the electrode side of the electrode substrate (1) for the electrolyte to flow from the electrode side to the diaphragm side; The confluence holes (2) are formed by carbonizing and forming holes on the surface of the electrode substrate (1) using a pore-forming filler.
2. A carbon fiber-based electrode for a flow battery according to claim 1, characterized in that: The density of the confluence holes (2) is 1-15 per cm 2 ; Preferably, the diameter of the confluence hole (2) is 0.2-3 mm.
3. A carbon fiber-based electrode for a flow battery according to claim 1, characterized in that: The thickness of the electrode substrate (1) is 0.5-5 mm; Preferably, the depth of the collecting hole (2) is at least half the thickness of the electrode substrate (1).
4. A method for preparing a carbon fiber-based electrode for a flow battery, characterized in that: The method comprises the following steps: Selecting an electrode substrate raw material, and inserting a pore-forming filler on the surface of the electrode substrate raw material; Carbonizing the electrode substrate raw material with the pore-forming filler inserted therein, so that a pore structure is formed at a portion of the surface of the electrode substrate raw material with the pore-forming filler inserted therein; The electrode substrate raw material containing the pore structure is graphitized to obtain the carbon fiber-based electrode for the liquid flow battery.
5. The method for preparing a carbon fiber-based electrode for a flow battery according to claim 4, characterized in that: The electrode substrate raw material is a carbon-based precursor material; The carbon-based precursor material is polyacrylonitrile-based carbon felt, polyacrylonitrile-based graphite felt, polyacrylonitrile-based carbon cloth or polyacrylonitrile-based carbon paper; Preferably, the thickness of the carbon-based precursor material is 0.8-10 mm.
6. The method for preparing a carbon fiber-based electrode for a flow battery according to claim 4, characterized in that: The method further comprises: before inserting the pore-forming filler into the surface of the electrode substrate raw material, performing a pre-oxidation treatment on the electrode substrate raw material; The pre-oxidation treatment conditions are: oxidation treatment at 270-290° C. for 85-95 minutes in an air atmosphere.
7. The method for preparing a carbon fiber-based electrode for a flow battery according to claim 4, characterized in that: The pore-forming filler is made of a material that does not deform during high-temperature sintering and does not undergo carbonization reaction; Preferably, the pore-forming filler is made of carbon-based material; Further preferably, the pore-forming filler is a carbon fiber bundle or a high-carbon needle.
8. The method for preparing a carbon fiber-based electrode for a flow battery according to claim 4, characterized in that: The diameter of the pore-forming filler is 1-3 mm; Preferably, the penetration depth of the pore-forming filler is at least half of the thickness of the electrode substrate raw material.
9. The method for preparing a carbon fiber-based electrode for a flow battery according to claim 4, characterized in that: The conditions of the carbonization treatment are: The carbonization temperature is 950-1050°C and the carbonization time is 1.8-2.2h; Preferably, the carbonization treatment is carried out under a protective atmosphere.
10. The method for preparing a carbon fiber-based electrode for a flow battery according to claim 4, characterized in that: The conditions of the graphitization treatment are: The graphitization treatment temperature is 1900-2300°C, and the graphitization treatment time is 1-3h; Preferably, the graphitization treatment is performed under a protective atmosphere.
Citation Information
Patent Citations
Combination electrode for all vanadium redox flow battery and preparation thereof
CN101335349A
All-vanadium flow battery porous carbon fiber felt electrode material and preparation and application thereof
CN105762369A
Vanadium battery electrode and vanadium battery
CN109167082A
Electrode and redox flow battery
CN110036513A
Method of manufacturing electrode for thin redox flow battery
CN110676476A
